A Clinical Practice Guideline for the Use of Ankle-Foot Orthoses and Functional Electrical Stimulation Post-Stroke. Issue 2 (April 2021) - Johnston, Therese E.; Keller, Sarah; Denzer-Weiler, Caitlin; Brown, Lisa
Abstract : Background: Level of ambulation following stroke is a long-term predictor of participation and disability. Decreased lower extremity motor control can impact ambulation and overall mobility. The purpose of this clinical practice guideline (CPG) is to provide evidence to guide clinical decision-making for the use of either ankle-foot orthosis (AFO) or functional electrical stimulation (FES) as an intervention to improve body function and structure, activity, and participation as defined by the International Classification of Functioning, Disability and Health (ICF) for individuals with poststroke hemiplegia with decreased lower extremity motor control. Methods: A review of literature published through November 2019 was performed across 7 databases for all studies involving stroke and AFO or FES. Data extracted included time post-stroke, participant characteristics, device types, outcomes assessed, and intervention parameters. Outcomes were examined upon initial application and after training. Recommendations were determined on the basis of the strength of the evidence and the potential benefits, harm, risks, or costs of providing AFO or FES. Results/Discussion: One-hundred twenty-two meta-analyses, systematic reviews, randomized controlled trials, and cohort studies were included. Strong evidence exists that AFO and FES can each increase gait speed, mobility, and dynamic balance. Moderate evidence exists that AFO and FES increase quality of life, walking endurance, and muscle activation, and weak evidence exists for improving gait kinematics. AFO or FES should not be used to decrease plantarflexor spasticity. Studies that directly compare AFO and FES do not indicate overall superiority of one over the other. But evidence suggests that AFO may lead to more compensatory effects while FES may lead to more therapeutic effects. Due to the potential for gains at any phase post-stroke, the most appropriate device for an individual may change, and reassessments should be completed to ensure the device is meeting the individual's needs. Limitations: This CPG cannot address the effects of one type of AFO over another for the majority of outcomes, as studies used a variety of AFO types and rarely differentiated effects. The recommendations also do not address the severity of hemiparesis, and most studies included participants with varied baseline ambulation ability. Summary: This CPG suggests that AFO and FES both lead to improvements post-stroke. Future studies should examine timing of provision, device types, intervention duration and delivery, longer term follow-up, responders versus nonresponders, and individuals with greater impairments. Disclaimer: These recommendations are intended as a guide for clinicians to optimize rehabilitation outcomes for people with poststroke hemiplegia who have decreased lower extremity motor control that impacts ambulation and overall mobility. A Video Abstract is available as supplemental digital content from the authors (available at: http://links.lww.com/JNPT/A335 ). Abstract : Supplemental Digital Content is Available in the Text.